Molecular Gut-Content Analysis of Adult Ground Beetles (Coleoptera: Carabidae) Provides No Evidence of Predation of Western Corn Rootworm (Coleoptera: Chrysomelidae) in a Nebraska Corn Agroecosystem - Oliveira-Hofman, Camila; Victor, Vinicius S. [UNESP]; Meinke, Lance J.; Peterson, Julie A. (Georgia Entomological Soc Inc, 2020)
This study was conducted to characterize the ground beetle (Coleoptera: Carabidae) community in Nebraska continuous cornfields and investigate the potential for predation of the western corn rootworm, Diabrotica virgifera virgifera LeConte, a key root-feeding insect pest that is an annual management challenge in this system. Seven collection dates were conducted at five commercial cornfields in west central Nebraska during the growing season of 2014. In each field, carabids were sampled using five 24-h pitfall traps. Carabid specimens were placed in 95% ethanol in the field and stored at 20 degrees C to preserve DNA. After identification to the species level, DNA was extracted and polymerase chain reaction was conducted for gut-content analysis using D. v. virgifera-specific primers. Data from single-plant emergence cages and yellow sticky cards showed high abundance of D. v. virgifera prey in three of the five fields sampled. Sixteen genera and 36 carabid species were found in pitfall traps. Of the total 235 carabid specimens tested in this study, zero tested positive for D. v. virgifera DNA. The lack of positive results for the presence of D. v. virgifera DNA in the gut-contents of carabids, despite abundant pest populations. indicates that, in this system, ground beetles may not be a strong mortality agent of D. v. virgifera. However, results presented here contribute to our knowledge of carabid diversity in agroecosystems and indicate that future D. v. virgifera biological control efforts in this region should focus on other natural enemies and/or other life stages of carabids, such as larvae.
Keywords: Carabidae; Diabrotica virgifera virgifera; rootworm; molecular gut-content analysis; field corn